The Influence of YouTube Educational Content as a Learning Medium on Students' Learning Interest Regarding the Excretory System Topic for Grade XI Science (IPA) at MA Ma’arif NU Jenggawah, Jember, in the 2025/2026 Academic Year. - Ahmad Sya’roni; Risma Nurlim (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Learning interest is one of the important factors that influence the success of the learning process. The low learning interest of students in Biology subjects, especially on the excretory system material, becomes a challenge that needs to be addressed through the use of innovative learning media. This study aims to analyze the effect of YouTube educational media on students' learning interest in the excretory system material for 11th grade science students at MA Ma’arif NU Jenggawah Jember in the 2025/2026 Academic Year. The study uses a quantitative approach with a quasi-experimental type. The research sample consists of an experimental class that receives learning using YouTube educational media and a control class that receives conventional learning. The research instrument is a learning interest questionnaire that has been tested for validity and reliability with a Cronbach’s Alpha value of 0.909. Data analysis was conducted using homogeneity tests and the Mann-Whitney U test with the assistance of SPSS version 32. The study results show that the average learning interest of students in the experimental class was 69.16, higher than the control class at 52.43. The Mann-Whitney U test results obtained an Asymp. Sig. (2-tailed) value < 0.001, indicating a significant difference between the two groups. Thus, the educational media on the YouTube platform has a significant effect on students' learning interest in the excretory system material. The use of YouTube can increase students' attention, interest, motivation, and involvement in the Biology learning process.